2010
DOI: 10.1590/s0080-62342010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Work and health conditions of sugar cane workers in Brazil

Abstract: RESUMOTrata-se de uma pesquisa exploratória, com abordagem quantitativa dos dados, realizada no intuito de analisar as situações de trabalho e de vida que podem oferecer riscos à saúde de trabalhadores envolvidos no corte manual e mecanizado da cana-de-açúcar. A amostra foi composta por 39 cortadores de cana e 16 operadores de colhedeiras. A coleta de dados ocorreu nos meses de julho e agosto de 2006, utilizando-se a técnica de observação direta das situações de trabalho e moradia dos trabalhadores, e por meio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
27

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 8 publications
0
40
1
27
Order By: Relevance
“…Eric Ries (2011) is credited with applying lean principles to founding start-ups. The lean start-up method is an iterative and agile method to develop a start-up based on listening to the needs of potential customers and testing their willingness to pay for the service or product offered by the start-up.…”
Section: Business Modelmentioning
confidence: 99%
“…Eric Ries (2011) is credited with applying lean principles to founding start-ups. The lean start-up method is an iterative and agile method to develop a start-up based on listening to the needs of potential customers and testing their willingness to pay for the service or product offered by the start-up.…”
Section: Business Modelmentioning
confidence: 99%
“…Further health problems self-reported in excess by the noise-exposed group included hypertension, headache, and sleep disturbance (Rao, Avvaru, and Krishna 2015). Rocha, Marziale, and Hong (2010) conducted structured interviews of Brazilian sugar industry workers (39 manual sugar cane operators and 16 mechanical harvester operators). Outcomes revealed that harvester operators often work in "high-noise conditions" [not quantified] for 10-h shifts for 11 days straight.…”
Section: Introductionmentioning
confidence: 99%
“…The whole processes are done manually by the workers and so most of them are suffering from different types of occupational health problems mainly work-related musculoskeletal disorders (WMSDs). [3,4] WMSDs are one of the most important causes for occupational hazards which not only affects the workers' efficiency and health conditions but also at the same time it decreases the production rates and waste millions of working hours. [5][6][7][8] Many researchers have reported about the strong association between awkward working postures and WMSDs [9][10][11][12][13][14][15] Several studies have also shown that some others factors such as age, education level, working experience, smoking, and alcohol consumption can also affect the musculoskeletal system of the workers.…”
Section: Introductionmentioning
confidence: 99%